Evaluation of the Economic Criteria for the Survival of Small Farms in Serbia - Ristanovic, Vladimir; ToÅ¡oviÄ‡-StevanoviÄ‡, Aleksandra (International Review of Management and Marketing, 2020)
Agriculture is an important economic sector in Serbia with the largest percentage of small and family farms. In order to improve this business and the survival of small farms in Serbia, the goal of the paper is to select the criteria for the survival of small farms in Serbia by applying the concept of analytical hierarchical processes (the AHP method). The research was conducted in Serbia on the sample of 550 small farms, comparing economic indicators based on the criteria that can contribute to achieving the goals of agricultural enterprises. Each indicator was evaluated and considered in relation to the set criteria, such as investments in farms, information available to farms, distribution channels of agricultural products, and the quality of agricultural products. The results of the survey showed that the best ranked indicator of the survival of small farms in Serbia is the level of education and knowledge of farmers, holders of farms. Keywords: Agro-business, The Analytical Hierarchical Processes Method, Economic Indicators, Analysis and Decision Making JEL Classifications: D710, Q120, Q130 DOI: https://doi.org/10.32479/irmm.10032